Investigation into the synergistic effects in hydrated gelling systems containing fly ash, desulfurization gypsum and steel slag. (30th October 2018) - Duan, Siyu; Liao, Hongqiang; Cheng, Fangqin; Song, Huiping; Yang, Hengquan
Highlights: There had a good synergistic effect in hydrated gelling systems containing FA, SS and FGD. The observed the synergy effect between FA, FGD and SS was attributed to produce more C-S-H gel and promote the secondary reaction of C-S-H. Abstract: This paper presented the synergistic effects with respect to compressive strength in hydrated gel systems containing fly ash (FA), flue gas desulfurization gypsum (FGD) and steel slag (SS). The compressive strength of ternary, binary and unary gel system blocks were primarily investigated, and then the block of highest compressive strength in each gel system was selected to optimize its ratio of raw materials. The results showed that the compressive strength of the complex gel blocks in different gel systems changed as follows: ternary system > binary system > unary system, in addition, the blocks with highest compressive strength in binary and unary systems were SS-FA gel block and SS gel block. Due to the optimized ratio of raw materials, there was an enhancement of compressive strength for binary (SS-FA) and ternary system blocks. For a ternary mixture containing 20% FA, 70% SS and 10% FGD, the synergistic effect was observed mostly at 28 days and it resulted in the highest compressive strength and lowest water absorption. Studies water durability revealed the gel blocks submerged in distilled water exhibited better strength development than that cured in air-dry. In this study, XRD, SEM and TGA were used to analyze the mineral composition, microstructure and thermal weight loss characteristics of different gel system blocks in order to determine the source of the synergy and quantify its magnitude. The results indicated that the observed the synergy effect between FA, FGD and SS was attributed to produce more hydrated calcium silicate (C-S-H) and new hydration products (eg. ettringite and C-S-H with a low calcium silicon ratio).